The epidemiological situation in Ukraine in terms of the implementation of preventive vaccinations according to the Protective Vaccination Program - Pachnia, Agnieszka; Drop, Bartlomiej; Polz-Dacewicz, Malgorzata (Current Issues in Pharmacy and Medical Sciences, 2022)
The level of immunization of children and adolescents under the Protective Vaccination Program in Ukraine is lower than in Poland, and, due to the outbreak of the war in Ukraine, many people now live in conditions that are often unsanitary. Centers for refugees are also places of increased risk of outbreaks of infectious diseases. This risk is increased by the low percentage of the vaccinated, limited access to healthcare (including diagnostics) and overcrowding. The paper presents the state of vaccination in Ukraine against poliomyelitis, measles, diphtheria, tetanus and pertussis, the most important problems in the field of infectious diseases, as well as the resulting risks and the need to prevent them.